Teacher Burnout as a Barrier to Social-Emotional Support in Early Childhood Education: A Case Study - Fitri Fitri; Tria Marini; Mar'atus Sholihah; Desmawati Roza (Indonesian Journal of Early Childhood Educational Research (IJECER), 2026)
Burnout among early childhood education (ECE) teachers significantly affects teacher-child interactions and the quality of social-emotional support. This study aimed to examine how teacher burnout functions as a barrier to the provision of social-emotional support in early childhood education by identifying its forms, underlying causes, and consequences for teacher-child interactions. This qualitative case study explores the forms, triggers, and consequences of burnout among eight purposively selected ECE teachers in Rao Selatan District, Pasaman Regency, Indonesia. Data were collected through semi-structured in-depth interviews and analyzed using thematic analysis involving coding, categorization, and theme development. Trustworthiness was strengthened through source triangulation, member checking, and peer debriefing. Findings revealed four key barriers: diminished relational sensitivity, psychological disengagement, helplessness in managing dual roles, and parental pressure arising from unrealistic academic expectations. These barriers collectively weakened teachers’ ability to provide effective social-emotional support. The study highlights the importance of systemic interventions, including administrative reform, teacher mental health support, and contextual professional development programs to improve teacher well-being and educational quality.